Aortic Arch Thrombosis Mimicking Interrupted Aortic Arch. (22nd April 2013) - Neal, Richard; Mattishent, Katharina; Reynolds, Fiona
Abstract : We report a case of a 32-week-gestation male who presented initially with symptoms suggestive of an interrupted aortic arch. The absence of a VSD prompted further investigations, including a CT angiogram, which revealed that he had an extensive thrombus in his aorta. He underwent a successful aortic thrombectomy with arch repair on cardiopulmonary bypass support. In view of the extensive thrombus, the patient was referred to the haematology team. There was no family history of prothrombotic tendencies.